High-Level Expression and Biochemical Properties of A Thermo-Alkaline Pectate Lyase From Bacillus sp. RN1 in Pichia pastoris With Potential in Ramie Degumming - Zheng, Xueyun; Zhang, Yimin; Liu, Xiaoxiao; Li, Cheng; Lin, Ying; Liang, Shuli (Frontiers in Bioengineering and Biotechnology, 2020)
Pectate lyases play an essential role in textiles, animal feed, and oil extraction industries. Pichia pastoris can be an ideal platform for pectate lyases production, and BspPel (a thermo-alkaline pectate lyase from Bacillus sp. RN1) was overexpressed by combined strategies, reaching 1859 U/mL in a 50 L fermentator. It displayed the highest activity at 80 ℃, and maintained more than 60% of the activity between 30 and 70°C for 1 h. It showed an optimal pH of 10.0, and exhibited remarkable stability over a wider pH range (3.0-11.0), retaining more than 80.0% of enzyme activity. The Km and kcat of BspPel on PGA was 2.19 g L-1 and 116.1 s-1, respectively. The activity was significantly enhanced by Ca2+, Mn2+ and Cu2+, and a slight increase was observed with the addition of Ba2+ and Mg2+. Scanning electron microscope was used to show the degumming efficiency of BspePel on ramie fibers. The loss weight was 9.2% when treated with crude enzyme supernatant and 20.8% when treated with the enzyme-chemical method, which was higher than the 14.2% weight loss in the positive control treated with 0.5% (w/v) NaOH alone. In conclusion, BspPel could be a good candidate for the ramie degumming industry.